2014
DOI: 10.1136/bcr-2013-200532
|View full text |Cite
|
Sign up to set email alerts
|

Atypical presentation of thoracic spondylodiscitis caused byStreptococcus mitis

Abstract: SUMMARYSpondylodiscitis, which is most commonly caused by Staphylococcus aureus, is an uncommon infection in adults. The diagnosis of spondylodiscitis is often delayed by its vague and non-specific presentations. As part of the normal flora in human mouth and sinuses, Streptococcus mitis is a very rare cause of spondylodiscitis. We report a case of thoracic spondylodiscitis caused by S. mitis in a patient with chronic sinusitis. The patient atypically presented with a sharp chest pain that radiated to the back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…Furthermore, Mehra underscores the significant role of odontogenic factors in chronic sinusitis, suggesting that dental conditions like periodontitis may impact sinus health via alterations in the oral microbiome's composition (Mehra and Jeong, 2009). The detection of Streptococcus mitis in chronic sinusitis patients' sinuses corroborates its contributory role in the condition's inflammation and pathogenesis as an oral microbiota component (Paju et al, 2003;Cariati and Deng, 2014). Likewise, the enrichment of Rothia mucilaginosa in these patients' sinus microbiota indicates its potential involvement in the disease's pathology, aligning with our research findings (Yuan et al, 2020).…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, Mehra underscores the significant role of odontogenic factors in chronic sinusitis, suggesting that dental conditions like periodontitis may impact sinus health via alterations in the oral microbiome's composition (Mehra and Jeong, 2009). The detection of Streptococcus mitis in chronic sinusitis patients' sinuses corroborates its contributory role in the condition's inflammation and pathogenesis as an oral microbiota component (Paju et al, 2003;Cariati and Deng, 2014). Likewise, the enrichment of Rothia mucilaginosa in these patients' sinus microbiota indicates its potential involvement in the disease's pathology, aligning with our research findings (Yuan et al, 2020).…”
Section: Discussionmentioning
confidence: 88%
“…Streptococcus mitis (S. mitis) has been individually identified as a part of the normal oropharyngeal flora, and has been mostly reported in cases of bacterial endocarditis and lung abscess through the bloodstream or respiratory tract [16][17][18][19]. On the other hand, there are a few rare cases of urinary tract infection, spondylodiscitis, and empyema caused by S. mitis [20][21][22]. Although the cause of infection around PTFE sheet in the present case was unclear because of no odontogenic infection and negative of the blood culture was negative, it is considered an extremely rare case.…”
Section: Discussionmentioning
confidence: 99%
“…10 12 Cariati et al described a thoracic spondylodiscitis in a patient with chronic sinusitis. 13 Feder and Gruson reported a case of glenohumeral infection, 14 Nomura et al reported an osteomyelitis of a lower extremity bone in a child. 15 Yusuf and colleagues 16 and Cinar et al 17 published cases of pelvic ring infections.…”
Section: Discussionmentioning
confidence: 99%